PENGGUNAAN GOOGLE FORM SEBAGAI MEDIA EVALUASI PEMBELAJARAN PADA MATA PELAJARAN KOMPUTER AKUNTANSI KELAS XI - Widodo, Muhammad; Genjik, Bambang; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to find out how to use Google Forms as a learning evaluation medium. The research location was conducted at SMK Negeri 3 Pontianak. The research conducted is a qualitative research with a descriptive approach. Data collection techniques were carried out by interviewing and documentation techniques. Data validity test was carried out using source triangulation. Data analysis techniques include domain, taxonomy, componential, and cultural theme analysis. The results of the study show (1) Planning to use Google Form as a learning evaluation medium is done by preparing a Gmail account, preparing questions, answer keys and scoring, inputting questions into Google Form and distributing question links to students. (2) The teacher gives instructions to students to prepare equipment such as an Android cellphone, a stable data network, student e-mail accounts and provides links to questions to work on. (3) excess is more efficient, effective, has a high level of objectivity, and is free to use. The drawback is that you have to have an Android cellphone, internet network, and a Gmail account. (4) The use of Google Forms is very effective, especially in conducting distance learning, and can reduce costs, time and effort in its implementation.